Strategic management of the African swine fever - Mirela Daniela Nicola; Dorina Nicoleta Mocuta (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
African swine fever (ASF) is a disease with a devastating impact on economy, affecting seriously the pig industry production and trade, discouraging farmers to restock their farms and continuing their business, overall changing policies and markets. In the last five years the ASF has badly affected the world: 50 countries affected on 4 continents, about quarter of pig world population died or was killed in order to control the disease, and millions of euro were paid to manage (eradicate) the disease. Despite the new policies, the overall management, the preventive and control measures taken, the disease is continuing to spread and leave behind huge losses into the global pork industry. In essence the paper aims to review experience on the management of ASF in affected countries and Romania and try to identify what went wrong in the management of the ASF and how countries can be better organized to react to an outbreak of African Swine Fever and to identify better ways to diminish the devastating impact of the disease upon societies, consumer, trade between the countries, economy.
Keywords: H12; Q18; 330; animal health; crisis management; risk factors; economy; trade